Analysis of selected kinematic variables of the take-off in ski jumps in the finals of the World Cup '99 at Planica - Jost, B.; Eoh, M.; Pustovrh, J.; Ulaga, M. (Kinesiologia Slovenica, 1999)
The objective of the study was to establish, by means of a 2-D kinematic analysis, the correlation between the selected kinematic parameters of the take-off of the jumpers and their performance from the aspect of the jump length, on a sample of the best ski jumpers (first series n = 42; second series n = 30) participating in the final competition of the World Cup in Ski Flights at Planica in 1999 (K 180 m).